IMPLEMENTATION OF FISHERIES UMKM POLICY IN SIMEULUE REGENCY - Ikhsan Ikhsan; Cut Asmaul Husna; Agus Pratama (DIA: Jurnal Administrasi Publik, 2022)
The fisheries sector is one of the leading sectors in Simeulue Regency's economy. It impacts increasing regional income, opening up employment opportunities, and improving the local community's standard of living, so fisheries UMKM policies are an important aspect of Simeulue Regency. The research method was descriptive qualitative, with field studies and interviews with policymakers and implementers from the Department of Marine Affairs and Fisheries (DKP), the Department of Industry, Trade, Cooperatives, and Small and Medium Enterprises (Disperindagkop) Simuelue Regency, and business actors. Furthermore, data were obtained through literature studies, which included scientific journals, government regulations, documents, and research reports. This study's analysis employs inductive logic by collecting field data and then analyzing it to conclude. The findings demonstrated that the government implemented the fisheries UMKM policy by providing business capital stimulus for UMKMs, conserving marine areas to protect fishery products, and limiting foreign ship visits to maintain marine sovereignty. The study concludes that the implementation of fisheries UMKM policies fails because: (1) there is no definite data on the number of fisheries UMKMs; (2) there is no communication and forum that can mediate the interests of UMKM business actors and the government; and (3) the government has limited budget funds in the form of business capital; and (4) UMKM business assistance and training have been provided, but have not yielded maximum results due to a lack of a market that can accommodate production results.